2003
DOI: 10.1152/ajpregu.00378.2002
|View full text |Cite
|
Sign up to set email alerts
|

The spleen modulates the febrile response of guinea pigs to LPS

Abstract: The febrile responses of splenectomized (Splex) or sham-operated (Sham) guinea pigs challenged intravenously or intraperitoneally with lipopolysaccharide (LPS) 7 and 30 days after surgery were evaluated. FITC-LPS uptake by Kupffer cells (KC) was additionally assessed 15, 30, and 60 min after injection. LPS at 0.05 μg/kg iv did not evoke fever in Sham animals but caused a 1.2°C core temperature (Tc) rise in the Splex animals. LPS at 2 μg/kg iv induced a 1.8°C greater Tc rise of the Splex animals than of their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 31 publications
4
25
0
Order By: Relevance
“…(3) We have shown recently that the onset of LPSinduced fever in guinea pigs is temporally related, irrespective of its routes of administration (intravenous or intraperitoneal), to the appearance of LPS in the liver and its uptake by Kc [72,73], suggesting that the complement system may be activated by contact with LPS in the liver rather than in the bloodstream. This, in turn, suggests that C5 may be generated independently of a plasma-derived complement system, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…(3) We have shown recently that the onset of LPSinduced fever in guinea pigs is temporally related, irrespective of its routes of administration (intravenous or intraperitoneal), to the appearance of LPS in the liver and its uptake by Kc [72,73], suggesting that the complement system may be activated by contact with LPS in the liver rather than in the bloodstream. This, in turn, suggests that C5 may be generated independently of a plasma-derived complement system, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we (9) found that removal of the spleen of guinea pigs results in significantly enhanced febrile responses to both iv and ip LPS, and that these hyperpyrexias are associated with an increased uptake of LPS by KC. These effects, moreover, are persistent because their robustness is undiminished 30 days after splenectomy.…”
mentioning
confidence: 83%
“…Unlabeled LPS was Salmonella enteritidis LPS B (batch no. 651628; Difco Laboratories, Detroit, MI), the same LPS batch we used in our previous studies (9,15). The vehicle for all solutions was pyrogenfree saline (PFS, 0.9% NaCl, USP; Abbott Laboratories, Chicago, IL).…”
Section: Drugsmentioning
confidence: 99%
“…Moreover, since the liver contains the body's largest population of mononuclear phagocytes (Kupffer cells, Kc), it is the primary clearinghouse of circulating LPS and therefore also the principal source of LPS-induced cytokines; the pyrogenic signal should therefore originate there. Indeed, the essential role of Kc in fever production was recently verified (Feleder et al, 2003;. Furthermore, a number of studies have now established that the subdiaphragmatic section of both vagal trunks, and its hepatic branches in particular, significantly attenuates the febrile response to LPS Sehic and Blatteis, 1996;Romanovsky et al, 1997a, b;Fleshner et al, 1998;Gaykema et al, 1998;Simons et al, 1998;Wieczorek et al, 2005), albeit that it is still controversial whether this effect is conditional on the route and dose of LPS administered (Goldbach et al, 1997;Hansen et al, 2001).…”
Section: Pyrogen Activation Of the Brain: The Role Of The Vagusmentioning
confidence: 99%